Assessment of impact of technology innovation on procurement transparency in selected public sector in South-East Nigeria - Jude Aleakhue; Kelechi Enyinna Ugwu; Hyacinth Iwu (YAYASAN MITRA PERSADA NUSANTARA, 2026)
This research study assessed the influence of technology on procurement transparency in selected public sector in South-East, Nigeria. The study employed the survey method, and a stratified random sampling technique to ensure representation of study population such as procurement, audit, finance, and administrative departments. Questionnaires were administered via face-to face to the study participants. Descriptive and inferential statistics using Pearson correlation techniques, simple regression techniques analysis of variance (ANOVA) were utilised to test hypotheses and determine the strength and direction of relationships between variables. Empirical evidence from research hypothesis one showed that e-tendering significantly influences transparency in decision making in the selected public sector. The study recommends public agencies to formally adopt and integrate e-tendering mechanisms into procurement frameworks to ensure standardized transparency. Procurement regulatory bodies should design policies that mandate ethical compliance in e-tender processes, minimizing loopholes that could weaken integrity.